Efektifitas Sistem Pelayanan Haji dan Umroh Dalam Meningkatkan Kepuasan Jamaah di PT. Safara Layanan Utama Probolinggo - Hafida Firdaus; Abd Aziz; Abd Ghafur (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2023)
This research aims to analyze the effectivity of PT. Safara Layanan Utama in providing services to increase congregation satisfaction, and to describe the supporting and inhibiting factors in the service at PT. Safara Layanan Utama. The research method used is descriptive qualitative method with data collection techniques namely interviews, observations which aim to describe, display, and explain data regarding service quality at PT. Safara Layanan Utama. Researchers conducted interviews with 6 informants, namely the congregation and employees. The results showed that services at PT. Main Service Safara has been good in many ways. Such as having professional employees, providing good facilities and infrastructure, being responsible for each congregation from registration, practicing umroh, and arrival, being able to serve appropriately, being able to communicate clearly, and being able to give trust to the congregation. Supporting Factors that described from the interviews a. Good Management. b. Quite strategic place. c. Good communication . d. Adequate Facilities. Inhibiting Factors: a. The number of employees is small. b. The office is a bit cramped, and never discriminate congregation. The guides were carried out patiently and painstakingly from the homeland until arriving at the holy land was carried out patiently and painstakingly so that the congregation felt satisfied.